MSME Lending And Bank Efficiency: Comparison Between Indonesia And Malaysia - Nugroho, Dwiyanjana Santyo; Aji, Tri Susilo Wahyu (JPS (Jurnal Perbankan Syariah), 2024)
MSMEs are one of the pillars of the country's economy; banking has a role in facilitating financing for MSMEs so that they can proliferate. On the other hand, banks must consider the cost efficiency they produce, considering that MSMEs are one of the sectors with high credit risk. This study aims to prove that financing for MSMEs can increase bank efficiency and that there are differences between banking in Indonesia and Malaysia. This study uses quantitative with an associative and comparative approach. The population of this study is banks listed on the Indonesia Stock Exchange and Bursa Malaysia in the 2020-2023 period. The Indonesian sample technique uses the purposive sampling method, and Malaysia uses the saturated sample method. The analysis technique uses stochastic frontier analysis (SFA), multiple linear regression, and difference tests with the help of statistical tools like Stata 17. The findings of the study show that financing for MSMEs affects bank efficiency. There is no difference between bank efficiency in Malaysia and Indonesia, but there is a significant difference between MSME financing in Malaysia and Indonesia. The theoretical implications of this study complement the theory regarding the relationship between MSME financing and bank efficiency. The practical implications of this research can provide recommendations to regulators in Indonesia to boost banking by increasing the financing ratio to MSMEs.